Physicians' understanding of antibiotic intravenous-to-oral switching-a qualitative study in Suzhou, China - Hui Zhang; Junjie Pan; Zhanhong Hu; Jie Pan; Hua Zhang (BMC, 2024)
Abstract Background The implementation of antibiotic intravenous-to-oral switch (IVOS) therapy in hospitals can slow down the development of drug resistance, reduce the occurrence of adverse reactions, and bring significant economic benefits. The aim of this study is to investigate the understanding of physicians at the Second Affiliated Hospital of Soochow University in Suzhou, China towards the antibiotic IVOS therapy. Methods 15 physicians working in 9 different departments of the Second Affiliated Hospital of Soochow University participated in this study. A semi-structured face-to-face interview was conducted to collect interview information about the antibiotic IVOS therapy. NVivo12 software was used to organize the entire interview content, and the interview data was analyzed and summarized using the Colaizzi seven step method. Results 60% of participants were not familiar with antibiotic IVOS therapy. Barriers of antibiotic IVOS therapy were included by three key issues: (i) Physicians' potential cognition: 'Iv is always better than oral'; (ii) Subjective infusion intention of patients; and (iii) Limitations of drug selection. 60% of participants expressed welcome for pharmacists to help them perform antibiotic IVOS treatment. And electronic recognition technology may be a feasible method for prompting IVOS conversion that recognized by all participants in the interview. Participants also provided some suggestions for pharmacists and IVOS computer reminders. Conclusion Physicians' in China still have insufficient understanding of antibiotic IVOS therapy. The promotion of antibiotic IVOS therapy in China faces many challenges and obstacles. Strategies such as IVOS therapy computer reminders and clinical pharmacists' medication guidance were worth studying to help physicians develop antibiotic IVOS treatment.